2019
DOI: 10.1186/s12909-019-1765-x
|View full text |Cite
|
Sign up to set email alerts
|

Changes of collective orientation through a medical student’s anaesthesia simulation course – simulation-based training study with non-technical skills debriefing versus medical debriefing

Abstract: Background Non-technical skills (NTS) are known to have a positive impact on quality of medical care. The team performance enhancing behaviour, as an example for NTS, is termed “Collective Orientation” (CO). In this study, we investigated the effect of a simulator-based anaesthesia training upon student’s CO in relation to medical and TeamGAINS (guided team self-correction, advocacy-inquiry and systemic-constructivist techniques) debriefing. We hypothesized (a) the scale collective orientation, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
(24 reference statements)
1
6
0
Order By: Relevance
“…This effect of changed CO does not seem to depend on professional experience, as we have made the same observation with experienced anesthesiologists before (21). As observed in a previous study, this effect does not occur, when the nurse is simulated by a physician (25). This simulation artifact is apparently not correctable and in uences the attitude of belonging to the team.…”
Section: Discussionsupporting
confidence: 79%
“…This effect of changed CO does not seem to depend on professional experience, as we have made the same observation with experienced anesthesiologists before (21). As observed in a previous study, this effect does not occur, when the nurse is simulated by a physician (25). This simulation artifact is apparently not correctable and in uences the attitude of belonging to the team.…”
Section: Discussionsupporting
confidence: 79%
“…Teamwork is crucial for success: varied backgrounds and interests enable them to solve the problems from different perspectives [34]. Eismann et al showed simulation courses have an in uence on teamwork [35]. This study found that the more closely learning context is related to real-life practices, the more mutual encouragement takes place among peers along with more positive feedback from the facilitator, which in turn promotes student engagement.…”
Section: Types and Characteristics Of Medical Student Engagementmentioning
confidence: 73%
“…Teamwork is crucial for success: varied backgrounds and interests enable them to solve the problems from different perspectives [32]. Eismann et al showed simulation courses have an in uence on teamwork [33]. This study found that the more closely learning context is related to real-life practices, the more mutual encouragement takes place among peers along with more positive feedback from the lecturer, which in turn promotes student engagement.…”
Section: Interaction With Realistic Learning Situationsmentioning
confidence: 74%